Culture of Speed on TikTok: Temporal Compression in Information Consumption among Indonesian Youth - Damien Amalaika Priambodo; Mochamad Ziaul Haq; Gerardette Philips (TEMALI : Jurnal Pembangunan Sosial, 2026)
This study examines how temporal compression in short-form TikTok videos shapes a culture of speed in the information consumption practices of Indonesian youth. The study employed an interpretive qualitative approach with a digital ethnographic orientation. This study collected data by analyzing 25 TikTok videos, conducting semi-structured interviews with 25 users aged 18–24, and examining seven-day digital-use diaries. The study analyzed the data through reflexive thematic analysis and qualitative content analysis. The findings show that temporal compression operates through pause removal and subtitle use (96% each), split-screen presentation (84%), rapid visual changes and high information density (68% each), and accelerated audio or video (56%). At the level of user experience, 80% of participants reported at least one form of temporal immersion, while 76% expected information to be delivered quickly and directly. The participants also demonstrated three patterns of information consumption: TikTok-only (36%), TikTok-first (28%), and cross-platform verification (36%). These findings highlight the need for digital literacy that also develops awareness of information rhythm, depth, and verification. The study’s originality lies in the concept of platformized temporal compression, which extends Social Acceleration by explaining the relationship among content compression, platform acceleration, users’ temporal adaptation, and the transformation of information practices.